The stressed eyewitness: the interaction of thematic arousal and post-event stress in memory for central and peripheral event information - Echterhoff, Gerald; Wolf, Oliver T. (Frontiers in Integrative Neuroscience, 2012)
Both arousal during the encoding of stimuli and subsequent stress can affect memory, often by increasing memory for important or central information. We explored whether event-based (thematic) arousal and post-event stress interact to selectively enhance eyewitnesses’ memory for the central aspects of an observed incident. Specifically, we argue that memory for stimuli should be enhanced when (a) the stimuli are encoded under arousal (vs. non-arousal), and (b) stress is experienced soon after the encoding episode. We designed an experiment that extended previous research by manipulating arousal without changing the stimulus material, distinguishing between central and peripheral event information, and using a dynamic, life-like event instead of static pictures. After watching a video depicting a burglary under high or low thematic arousal, psychosocial stress was induced or not induced by the Trier Social Stress Test. Salivary cortisol was measured at standard intervals. Consistent with our prediction, we found a significant thematic arousal x post-event stress x centrality interaction, indicating that the recognition advantage for central event items over peripheral event items was most pronounced under both high thematic arousal and post-event stress. Because stress was induced after encoding this interaction cannot be explained by possible differences at encoding, such as narrowed attention. The centrality effect of post-event stress under high thematic arousal was statistically mediated by the cortisol increase, which suggests a key role of the stress hormone. We discuss implications of our findings for psychological and neuroscientific theories of emotional memory formation.